H3K27me3 and HOXA9 expression predict prognosis in pediatric acute myeloid leukemia: an epigenetic-transcriptional correlation study - Goto, Hironori; Suenobu, Souichi; Koga, Yuhki; Yamamoto, Shunsuke; Nakashima, Kentaro; Oba, Utako; Hasegawa, Daiichiro; Usami, Ikuya; Yamamori, Ayako; Moritake, Hiroshi; Nobusawa, Sumihito; Okuno, Keisuke; et al. (Frontiers in Hematology, 2025)
BackgroundEpigenetic dysregulation plays a central role in pediatric acute myeloid leukemia (AML), yet its clinical relevance remains underexplored. This study primarily aimed to elucidate the clinical effect of H3K27me3 and H3K4me3 status on pediatric acute myeloid leukemia. We evaluated the prognostic impact of H3K27me3 and H3K4me3 histone trimethylation, along with associated gene expression profiles, in pediatric AML.MethodsWe retrospectively analyzed 74 children with newly diagnosed non-FAB M3 and non-Down syndrome AML in a prolonged cohort in Japan. Bone marrow immunohistochemistry assessed H3K27me3 and H3K4me3 expression levels. RNA sequencing was successfully performed on sorted leukemic blasts in six representative cases, owing to limited sample availability. Chemoresistance and epigenetic modulation were evaluated in AML cell lines treated with GSK-J4, a histone demethylase inhibitor.ResultsHigh H3K27me3 expression at diagnosis was significantly associated with superior overall and event-free survival over three years (OS HR 8.0; EFS HR 5.0; both p < 0.01). H3K4me3 levels at diagnosis showed no prognostic impact. Among 14 KMT2A-rearranged cases, all six patients with high H3K27me3 achieved a long-term first remission (median follow-up: 10 years), whereas those with low expression had higher relapse rates. Transcriptomic analysis revealed upregulation of HOXA9, and HOXA-cluster genes and downregulation of ABCB1, in low H3K27me3 samples. In vitro, GSK-J4 increased H3K27me3 and suppressed HOXA9 expression in KG-1 cells, enhancing sensitivity to cytarabine.ConclusionLow H3K27me3 expression defines a poor-risk group in pediatric AML, potentially via HOXA9-driven dysregulation. H3K27me3 may serve as a prognostic biomarker and potential therapeutic target.